Allogeneic haemopoietic cell transplant services in Australia and New Zealand in the first year of the COVID‐19 pandemic: a report from Australia and New Zealand transplant and cellular therapies. Issue 3 (16th September 2022) - Othman, Jad; Aarons, Donna; Bajel, Ashish; Butler, Jason; Doocey, Richard; O'Brien, Tracey; Purtill, Duncan; Smith, Lisa; Wilcox, Leonie; Hamad, Nada
Abstract: Background: The COVID‐19 pandemic has caused major disruption to health systems, with allogeneic haemopoietic cell transplant (alloHCT) services a particularly vulnerable area. Ongoing provision of alloHCT has required dynamic responses at national and local levels. In Australia and New Zealand (ANZ), a high reliance on unrelated donors from overseas registries has posed an additional challenge. Aims: To describe the impact of COVID‐19 on alloHCT services in ANZ in the first year of the pandemic. Methods: Data from the national alloHCT patient and unrelated donor registries were extracted for a 2‐year time frame. Comparisons were made between a pre‐pandemic period of 1 March 2019 to 29 February 2020 and the corresponding dates during the pandemic, 1 March 2020 to 28 February 2021. Results: There was a 13% decrease in the number of allogeneic transplants, a reversal of steady increases in previous years, with the largest decrease in unrelated donor transplants. Local donors supplied a greater proportion of unrelated stem cell products. With a switch to universal cryopreservation, the time from request of a product to infusion increased by a median of 25.5 days for overseas products and 14 days for local products. There was a significant increase in the number of products collected but not used. Conclusions: A strong public health response and coordinated transplant community activities allowed for safe provision of alloHCT in ANZ; however, our data suggest that the timely delivery of allogeneic transplants was affected by the COVID‐19 pandemic. Continued dedicated efforts are required to minimise further impacts.